X-ray and radio emission of kiloparsec jets at large redshifts - Mykhailova, M.S. (Advances in Astronomy and Space Physics, 2012)
For some jets of core dominant quasars we assumed that the X-ray emission of the nearest to the core knots is produced by the inverse Compton scattering on the quasar emission whereas the X-ray emission of distant knots is formed by the inverse Compton scattering on the cosmic microwave background as it takes place for the 3C 273 jet. Competition of the scattered radiation allows to estimate the luminosity of quasars and the angle between the jet and the line of sight. This angle for a jet of the quasar 1745+624 is 24° ÷ 34°. We found that the ratio of X-ray to radio flux densities conforms to the expected dependence on redshift for the knots of PKS 1127-14 and 1745+624 jets.